2012
DOI: 10.3928/00220124-20120615-44
|View full text |Cite
|
Sign up to set email alerts
|

The Emotional Intelligence Profile of Successful Staff Nurses

Abstract: The study findings suggested that successful staff nurses have average or higher levels of EI and that empathy among these nurses declines with age. Research on how empathy evolves, factors that influence empathy, and strategies to enhance EI among nurses is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 20 publications
3
35
3
Order By: Relevance
“…Age was not found to be associated with nurses' emotional intelligence in a study by Van Dusseldorp et al [31], in contrast to results from Harper & Jones-Schenk [33], who found that nurses' empathy diminished with age. Kahraman & Hiçdurmaz [34] found no significant differences between emotional intelligence scores in nurses based on demographic variables such as age, sex, marital status, or having children.…”
Section: Introductioncontrasting
confidence: 45%
“…Age was not found to be associated with nurses' emotional intelligence in a study by Van Dusseldorp et al [31], in contrast to results from Harper & Jones-Schenk [33], who found that nurses' empathy diminished with age. Kahraman & Hiçdurmaz [34] found no significant differences between emotional intelligence scores in nurses based on demographic variables such as age, sex, marital status, or having children.…”
Section: Introductioncontrasting
confidence: 45%
“…Previous research has demonstrated that emotional intelligence exerts a considerable effect on reducing occupational burnout (e.g. Görgens‐Ekermans & Brand, ; Harper & Jones‐Schenk, ). The present authors' power analysis suggested that a sufficient sample size is necessary to determine the effect of emotional intelligence as a boundary condition between occupational burnout and its effect on the quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have explored caring behaviors of nurses using self‐report measures (LiLi, Hong, Xian, & Qi, ); some have included comparative studies of caring behaviors by nurses and their first‐line managers (Peng, Liu, & Zeng, ), and by nurses and patients (Goh & Vehviläinen‐Julkunen, ; Papastavrou, Efstathiou, & Tsangari, ). Other factors explored that influence work performance or caring behaviors include resilience and self‐confidence (RNAO, ; Koen, Van Eeden, & Wissing, ), conscientiousness (Judge, ), and emotional intelligence (Harper & Jones‐Schenk, ; McQueen, ). Except for job involvement and work performance, there are limited previous studies exploring the influence of characteristics, such as values, personality, job involvement, and empathy, in relation to work performance and caring behaviors (Katrinli, Atabay, Gunay, & Guneri, ; Rafferty & Lindell, ; Roud, Giddings, & Koziol‐Mclain, ; Schwirian, ).…”
Section: Introductionmentioning
confidence: 99%